?PRODUCTIVITY OF RICE-WHEAT SYSTEM IN RELATION TOAZOLLA GREEN MANURE FERTILIZED WITH NITROGEN AND PHOSPHORUS (Biological Sciences - PJSIR, 1998)
Nitrogen contribution of Azalia fertilized with nitrogen (N) and phosphorus (P) in rice-wheat sequence was investigated in a greenhouse study. Rice yield was significantly increased over control when 100 mg N .kg:' soil alongwith 12 and 24 mg P kg' soil was applied in the absence of Azolla green manuring. The rice straw yield was significantly increased at both 50 and 100 mg N kg:' soil over control. Azalia green manure increased both the straw and grain yield significantly (P< 0.05) at all levels of Nand P application. Total N uptake followed the trend observed for straw and grain yield. The 50-12 mg N-P kg' soil alongwith Azolla green manure contributed 2 % of the total N to rice whereas by doubling the P application rate, N contribution increased to 50%. However, application of 100~24 mg N-P kg:' soil, the relative N contribution by Azolla sharply decreased to about 30 %_The highest residual N content in soil was observed where 100-24 mg N-P kg:' soil and Azolla green manure was applied. However, the highest P content of soil was observed which received 50-24 mg N-P kg-' soil. The residual effect of applied Nand P and Azolla green manuring significantly increased straw and grain yield of wheat in soil where 50-12, 50-24 and 100-24 mg N-P kg' soil were applied to rice crop as compared with control.